High-performance InGaAs-GaAs-AlGaAs broad-area diode lasers with impurity-free intermixed active region - Yan-Rui Zhao; Smolyakov, G.A.; Osinski, M. (IEEE journal of selected topics in quantum electronics, 2003)
Broad-area InGaAs-GaAs-AlGaAs double-quantum-well graded-index separate-confinement heterostructure lasers with as-grown and intermixed active regions were fabricated and characterized. An impurity-free vacancy diffusion method was used to intermix the quantum wells. Light-current characteristics of both types of lasers were used to extract information about the effects of intermixing process on threshold current density, internal optical loss, internal quantum efficiency, material gain, etc. Comparison between these parameters indicates comparable device performance, even though intermixing involved annealing at 1000/spl deg/C which resulted in a 42-nm wavelength blueshift.